Sapampangan celebrating the resilient identity of Angeles City through the Abacan disaster zone riverscape development - Morales, Irene D.
This study proposes how a designed landscape can affect the views of people on natural disasters. It shows how an intangible concept like resilience be used as the inspiration in developing open spaces from disaster zones. The goal of this study was to affect the consciousness of people by telling them actual stories that manifests this disaster resiliency using the landscape development as the narrative medium. Pampanga, specifically Angeles City was chosen to be the focus of this study due to its long history of disasters ; Mt. Pinatubo eruption being the worst so far. For this study, the Abacan River Disaster Zone Area in Angeles City, Pampanga was used as the sited and setting because of its vital role in times of past and future disasters. This study shall give an idea on how landscape narratives be used as a tool to influence the collective consciousness of a community and help them recover from disaster traumas. In the end, this study hopes to successfully communicate stories using landscape architecture as an instrument to shape the identity of the people as well as their culture on disaster resiliency.